Hidden Domination Mechanism in Student Intolerance Practices at Higher Education in Bima City - Syukurman, Syukurman; Syamsu A. Kamaruddin; Arlin Adam; Syamsidah, Syamsidah; Najamuddin, Najamuddin (Education Specialist, 2024)
This study examines the Mechanism of covert domination in the social practices of student intolerance in Higher Education (HE) in Bima City, with a focus on to investigate how covert domination in the social practices of student intolerance operates in HE at Bima City. The study uses a descriptive qualitative research method. This study began with data collection through various techniques such as in-depth interviews, observations, and document reviews. These data were then analyzed to find patterns of intolerant behavior and the social and cultural contexts that underlie them. The results of this study reveal organizational dominance, manipulation of student awareness, exclusion of minority groups, normalization of campus life, and neglect of minority religious practices. The results also show that the dominance of certain student organizations often creates a non-inclusive environment, where student awareness is manipulated to support certain agendas, resulting in the exclusion of minority groups. Minority religious practices are often ignored, which contributes to the normalization of intolerant campus life. Then in this study it was found that inclusive education and the formation of an equal community in realizing a more tolerant HE in Bima City.